Church History as Theological Discipline in the Context of Historical Education in the Synodal Period - Sukhova Nataliia (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article is dedicated to the history offormation and development ofchurch history in the Russian universities. The author pays attention to background of introduction of church history as independent discipline in the Russian universities; considers in detail, how the first teachers of church history at universities — I. M. Dobrotvorsky, archpriest A. M. Ivantsov-Platonov, I. E. Troitsky — understood her place and value at historical-philological faculties. The special attention is given to the problems connected with presence of church history, as theological science, in the context of historical education.